Strength of association between the Five‑Times‑Sit‑to‑Stand Test and balance, knee extensor strength and lower limb power in community‑dwelling older adults. (2019) - Tiwari, Devashish; Talley, Susan Ann; Alsalaheen, Bara; Goldberg, Allon
No abstract available